Unusual location of the glomus tumour in the liver: A case report and literature review. Issue 26 (June 2018) - Li, Liang; Xu, Qing-Xia; Zhang, Xiang-Yu; Han, Cui-Hong
Abstract: Rationale: Liver glomus tumor is very rare, and only 6 cases have been reported. Herein, we report another case of liver glomus tumor and the clinicopathological features are summarized. Patient concerns: An 18-year-old male patient was admitted due to hypertension and arrhythmia for 4 days. Diagnoses: Abdominal enhanced CT revealed a 6.0-cm solid and cystic mass in the left liver lobe. The mass was collected by hepatic lobectomy. Microscopically, the tumor cells were round or oval, and had no malignant features and no evident atypia. Immumohistochemically, tumor cells were positive for positive for SMA and vimentin, but partially positive for syn, CD34 and desmin. He was pathologically diagnosed with liver glomus tumor. Interventions: The patient underwent a left hepatic lobectomy. Outcomes: After surgery, this patient was followed up for 6 months, and metastasis/recurrence was not observed. Lessons: Primary liver glomus tumor has no specific clinical manifestations, and imaging examinations have limitations for its diagnosis. Immunostaining for SMA and vimentin is necessary to prove the diagnosis. Complete resection is strongly advised and it has a favorable prognosis.